Comparison of the effect of some plant powders on the protection of cowpea seeds from the infection of the southern cowpea beetle Callosobruchus maculates (Fab.) (Coleoptera:Bruchidae) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study was conducted in the insect lab / College of Agriculture, University of Baghdad and Technical College / Musayyib, for the purpose of knowing the effect of plant powders (officinale Zingiber, Cinnamon zeyalanicum, longa Curcuma, and limon Citrus) in the  weights 1, 3 and 5 g in some biological aspects of the cowpea beetle insect Callosobruchus maculates under laboratory conditions. The experiment included four treatments in addition to control treatment with three replicates and ten insects per replicate, The results of the study showed that turmeric powder is superior to larvae, giving the highest rate of 17.7% at the weight unit of 5 g. In addition, it is better than the used powders and all the weight units. Ginger powder also surpasses the rest of the powders in all weight units by germination rate of 96.7% The lemon peel powder gave the lowest percentage of germination at 76.7% compared to the 96.7% control treatment. The ginger powder showed a 100% repellent effect while the lemon peel powder achieved an attractive effect of 60% at the weight unit of 5 g.